The Effect Of Counsiling Program On The Psychological Climate Of Youth Handball Players Aged (17-18) Years Old - Ali, Abbas; Suleiman, Hamed; Jabbar, Sanaa (Journal of Physical Education, 2019)
The researchers realized that the problem of the study lies in paying attention to physical and skill aspects of sport while neglecting the psychological part. In addition to that there is no psychological specialist for sport teams that diagnose the psychological problems that the player goes through. Players themselves do not pay attention to the psychological aspect of his training a matter that negatively affects the players’ performance during competition. The aim of the research was to prepare a program for cognitive – behavioral counseling of youth handball players. The researchers used the experimental method on (14) players of Al-Anbar club in handball. The pretests were applied on Sunday 18/3/2018. The researchers concluded that there is a significant difference after applying cognitive – behavioral program in the psychological climate. In addition to that, they concluded high percentages in psychological climate variable in the subjects of the study before applying the program.